The Role Of Organizational Commitment In Mediating The Effect Of Employee Well-Being And Workload On Employee Performance: A Case Study Of ABC Company In Medan, Indonesia - Azzahra Syafitri Matondang, Ridha; Lumbanraja, Prihatin; Siahaan, Elisabet (Publisher Cv. Inara, 2023)
Over the last 5 years, ABC company in Medan has been experiencing a financial issue that led to several other problems such as the absence of employee performance appraisal, salary and compensation cuts which also have an impact on employee well-being, as well as the implementation of an early retirement program which has caused a number of employees to take part in the program thus impacting on high workload and decreased employee organizational commitment. Therefore, the present study aims to investigate and elucidate the effect of employee well-being and workload on employee performance through organizational commitment as a mediating variable at ABC Company Medan. Descriptive Quantitative was employed as a research design with Causal Associative as the methodological approach. The present study used both primary and secondary data that were obtained through a list of questionnaire statements and interviews as well as documentation studies. 58 employees of ABC Company Medan were the sample in this study which was selected using the Total Sampling technique or a saturated sampling out of 58 populations. The data analysis techniques using descriptive statistical analysis and path analysis, using Smart PLS. Based on the results, it was figured out that, directly, employee well-being has a positive and significant effect on both organizational commitment and employee performance. Organizational commitment has a positive and significant effect on employee performance. However, workload has a negative and significant effect on both organizational commitment and employee performance. Based on the Sobel Test, indirectly, employee well-being has a positive and significant effect on employee performance and workload has a negative and significant effect through organizational commitment as a mediating variable on employee performance.